FRI0301 GASTROINTESTINAL ADVERSE EVENTS IN PATIENTS WITH SYSTEMIC SCLEROSIS-ASSOCIATED INTERSTITIAL LUNG DISEASE (SSC-ILD) TREATED WITH NINTEDANIB: DATA FROM THE SENSCIS TRIAL. (June 2019) - Maher, Toby; Highland, Kristin; Gahlemann, Martina; Azuma, Arata; Fischer, Aryeh; Mayes, Maureen; Raghu, Ganesh; Sauter, Wiebke; Girard, Mannaig; Alves, Margarida; Clerisme-Beaty, Emmanuelle; Kohlbrenner, Veronika; et al.
Abstract : Background: In patients with idiopathic pulmonary fibrosis (IPF), nintedanib has a manageable adverse event (AE) profile characterised predominantly by gastrointestinal (GI) events. The efficacy and safety of nintedanib versus placebo in patients with SSc-ILD were investigated in the SENSCIS trial (NCT02597933 ). Objectives: To characterise GI AEs associated with nintedanib therapy in the SENSCIS trial. Methods: Patients with SSc-ILD with onset of first non-Raynaud symptom <7 years were randomised to receive nintedanib 150 mg bid or placebo double-blind. Dose reductions to 100 mg bid and treatment interruptions were allowed to manage adverse events. AEs reported over 52 weeks of treatment were coded using preferred terms in the Medical Dictionary for Regulatory Activities and analysed descriptively. A questionnaire was used to collect additional information on diarrhoea AEs. Results: A total of 576 patients (288 per group) received ≥1 dose of nintedanib or placebo. Over 52 weeks, 13.9% and 7.3% of patients treated with nintedanib and placebo discontinued study treatment due to AEs. The most frequent AEs in patients treated with nintedanib were diarrhoea (75.7% vs 31.6%), nausea (31.6% vs 13.5%) and vomiting (24.7% vs 10.4%). Serious diarrhoea AEs were reported in 2 patients (0.7%) in each group, and serious vomiting AEs were reported in 2 patients (0.7%) in the placebo group and none in the nintedanib group. Of the 218 nintedanib-treated patients who experienced a diarrhoea AE, most experienced events that were at worst of mild (49.5%) or moderate (45.0%) intensity, most (70.2%) experienced 1 or 2 events, and the duration of diarrhoea AEs was ≤9 days for 50% of the events reported over 52 weeks. Among nintedanib-treated patients who experienced ≥1 diarrhoea AE, 26.1% had a permanent dose reduction and 9.2% discontinued study drug due to the AE. Among the 91 patients in the placebo group who experienced ≥1 diarrhoea AE, the duration of diarrhoea AEs was ≤3 days for 50% of the events reported over 52 weeks, 2.2% had a permanent dose reduction and 1.1% discontinued study drug due to the AE. Conclusion: In patients with SSc-ILD, the gastrointestinal AEs associated with nintedanib were manageable for most patients and consistent with its known safety and tolerability profile in patients with IPF. Disclosure of Interests: Toby Maher Grant/research support from: Received funds from BI advisory board participation and conference travel. Received research funding and/or consulting fees or other remuneration from GSK, UCB, AstraZeneca, Roche, Bayer, Biogen Idec, Cipla, Prometic, and Sanumed. Toby Maher has, via his institution, received industry-academic funding from GlaxoSmithKline R&D and UCB., Consultant for: Toby Maher has received consultancy or speakers fees from Apellis, AstraZeneca, Bayer, Biogen Idec, Boehringer Ingelheim, Galapagos, GlaxoSmithKline R&D, Indalo, Pliant, ProMetic, Roche, Samumed and UCB; and has received consultancy fees from Galecto., Kristin Highland Grant/research support from: Kristin Highland is a site PI for the SENSCIS trial (Dr Highland's institution has the contract for the study) which is funded by Boehringer Ingelheim., Consultant for: Kristin Highland is a paid consultant for Boehringer Ingelheim through her role sitting on the steering committee., Speakers bureau: Kristin Highland is on the speakers' bureau for Boehringer Ingelheim., Martina Gahlemann Employee of: Employee of Boehringer Ingelheim, Arata Azuma Consultant for: Arata Azuma has received personal fees from Boehringer Ingelheim, Shionogi & Co., Ltd, Taiho Pharmaceutical Co., Ltd, and Asahikasei Pharma Co., Aryeh Fischer Grant/research support from: Aryeh Fischer has received a grant from Boehringer Ingelheim (Consultant/steering committee member/principal investigator on clinical trials)., Consultant for: Aryeh Fischer has received personal fees from Boehringer Ingelheim (Consultant/steering committee member/principal investigator on clinical trials), Genentech-Roche (Consultant/steering committee member/principal investigator on clinical trials), Pfizer (Consultant) and Genentech (Consultant)., Maureen Mayes Grant/research support from: Maureen Mayes is a clinical trial investigator for Boehringer-Ingelheim; Galapagos, Reata, Sanofi, Merck-Serono, Consultant for: Maureen Mayes is a member of scientific advisory boards for Galapagos NV (Pharma), Boehringer-Ingelheim, Mitsubishi-Tanabe, Astellas: Grant Review Board for Actelion., Speakers bureau: Maureen Mayes received personal fees for being a conference speaker on the use of autoantibodies in connective tissue diseases for Medtelligence, Ganesh Raghu Grant/research support from: Ganesh Raghu is the principal investigator for IPF net studies and is a steering committee member for IPF net studies for the NIH., Consultant for: Ganesh Raghu is a consultant for Boehringer Ingelheim, Bellerophan, Biogen, BMS, Fibrogen, Gilead, Nitto, Revistan, Promedior, Sanofi, Veracyte and Roche-Genentech; and a consultant and chair of the DSMB for Avalyn., Wiebke Sauter Employee of: Wiebke Sauter is an employee of Boehringer Ingelheim, Mannaig Girard Employee of: Mannaig Girard is an employee of Boehringer Ingelheim, Margarida Alves Employee of: Employee of Boehringer Ingelheim, Emmanuelle Clerisme-Beaty Employee of: Emmanuelle Clerisme-Beaty is an employee of Boehringer Ingelheim, Veronika Kohlbrenner Employee of: Veronika Kohlbrenner is an employee of Boehringer Ingelheim, Masataka Kuwana Grant/research support from: Actelion, Consultant for: Chugai, Reata, GlaxoSmithKline, Bayer, Boehringer-Ingelheim, Corpus, CSL-Berling, Mochida, Speakers bureau: Actelion, Pfizer, Bayer, Nippon Shinyaku, Chugai, Oliver Distler Grant/research support from: Prof. Distler received research funding from Actelion, Bayer, Boehringer Ingelheim and Mitsubishi Tanabe to investigate potential treatments of scleroderma and its complications, Consultant for: Prof. Distler has/had consultancy relationship within the last 3 years with Actelion, AnaMar, Bayer, Boehringer Ingelheim, ChemomAb, espeRare foundation, Genentech/Roche, GSK, Inventiva, Italfarmaco, iQvia, Lilly, medac, MedImmune, Mitsubishi Tanabe Pharma, Pharmacyclics, Novartis, Pfizer, Sanofi, Serodapharm and UCB in the area of potential treatments of scleroderma and its complications. In addition, he had/has consultancy relationship within the last 3 years with A. Menarini, Amgen, Abbvie, GSK, Mepha, MSD, Pfizer and UCB in the field of arthritides and related disorders